Therapeutic effects and mechanisms of plant-derived natural compounds against intestinal mucositis - Li, Cailan; Xie, Jianhui; Wang, Jiahao; Cao, Ying; Pu, Min; Gong, Qihai; Lu, Qiang (Frontiers in Pharmacology, 2022)
Intestinal mucositis is a clinically related adverse reaction of anti-tumor treatments. It is suffered by the majority of sick persons receiving treatments with high-dose chemical therapy, radio therapy and bone-marrow transplant. Clinical manifestations of intestine mucositis mainly include pain, body-weight reduction, inflammatory symptom, diarrhoea, hemoproctia and infection, which affect regular nutrition input and intestine function. Intestine mucositis often influences adherence to anti-tumor treatment as it frequently restricts sufferer’s capacity to tolerate treatment, resulting in schedule delays, interruptions or premature suspension. In certain circumstances, partial and general secondary infections are found, raising the expenditures on medical care and hospitalization. Current methods of treating intestinal mucositis are provided which do not always halt this disorder. Under this background, novel therapeutical measures are being investigated for the prevention and treatment of intestine mucositis. Natural products have lately become potential compounds against intestine injury by reason of the capacity to facilitate mucosa healing and their anti-inflammation effects. These roles are related to the improvement of intestinal mucosal barrier, inhibition of inflammatory response and oxidative stress, and adjustment of gut microflora and immunity system. The present paper aimed at systematically discussing the recent progress of natural products as promising treatments for intestine mucositis.